Analisis Pengaruh Pertumbuhan Ekonomi dan Belanja Modal terhadap Kemandirian Keuangan Daerah pada Provinsi di Pulau Jawa - Azzahra Mayraina; Nurul Badriyah (Cahaya Abadi Publisher, 2025)
Regional autonomy gives regional governments the authority to manage finances independently, including in terms of fiscal decentralization. Over the last decade, Regional Original Income (PAD) in Indonesia has increased by 100%. However, to measure whether this increase is sufficient for regional needs, the Regional Financial Independence Ratio (RKKD) is calculated. This research aims to analyze the influence of economic growth and capital expenditure on regional financial independence in the provinces of Java Island during the 2013–2023 period. The method used is multiple linear regression analysis with panel data from six provinces on the island of Java. The research results show that partially, economic growth has a positive and significant effect on regional financial independence. However, capital expenditure does not have a significant effect. Simultaneously, economic growth and capital expenditure have a significant effect on regional financial independence. These findings indicate that increasing economic growth can strengthen regional fiscal independence, especially through optimizing taxes and levies. However, the effectiveness of capital expenditure still needs to be improved to better support regional independence. The government is expected to focus more on increasing regional revenues through more effective tax collection strategies and more productive allocation of capital expenditure. In addition, fiscal policy should consider differences in economic potential between regions so that the distribution of transfer funds is more targeted.